An experimental investigation of the mechanical performance and structural application of LECA-Rubcrete. (30th June 2018) - Youssf, Osama; Hassanli, Reza; Mills, Julie E.; Abd Elrahman, Mohamed
Highlights: Mechanical properties and structural performance of LECA-Rubcrete were measured. Static cyclic loading was applied on reinforced concrete beams. Pre-treatment of LECA and rubber particle was carried out. Cement paste pre-treatment method showed the best strength enhancement. Rubcrete produced similar energy dissipation to that of conventional concrete. Abstract: Due to the high number of discarded end-of-life tyres around the world every year, the use of rubber waste in concrete has been researched for some years in normal and high strength concrete. Rubcrete is a type of concrete which is similar to conventional concrete, but uses scrap tyre rubber as a partial substitution for mineral aggregates. Lightweight concrete is another type of concrete with the advantage of reducing the self-weight of the structure. Utilizing rubber waste in concrete as a replacement of fine and/or coarse aggregates to produce lightweight concrete is of great interest as it can potentially provide a ductile lightweight concrete. This study investigates the possibility of using rubber waste, lightweight expanded clay aggregate (LECA), or a combination of both, in producing ductile lightweight concrete at the material level as well as the structural level. Fourteen concrete mixes were produced with different rubber content as replacement of fine aggregate volume, and different rubber/LECA content as replacement of coarse aggregate volume. The pre-treatment of the rubber/LECA particles using water, cement/silica fume paste, and cement/silica fume solution was also investigated. Three reinforced concrete beams with 130 mm × 230 mm cross-section and 1000 mm length were made out of selected mixes and tested under cyclic loading. Several rheological and mechanical properties, and structural performance characteristics were measured and compared. The results indicated that the LECA performs better than coarse rubber as a replacement for concrete coarse aggregate. Pre-treatment of fine rubber by soaking in water for 24 h had no significant effect on concrete slump; however, it increased the compressive strength by 15%. Rubcrete had an insignificant effect on the general behaviour of the reinforced concrete beams. Using LECA-Rubcrete decreased the strength and ultimate displacement of the reinforced beam by 22% and 21%, respectively compared with the Rubcrete beam.